Microwave-assisted pyrolysis of methyl ricinoleate for continuous production of undecylenic acid methyl ester (UAME). (June 2015) - Nie, Yong; Duan, Ying; Gong, Ruchao; Yu, Shangzhi; Lu, Meizhen; Yu, Fengwen; Ji, Jianbing
Graphical abstract: Highlights: A continuous microwave-assisted pyrolysis system was developed. UAME was produced from methyl ricinoleate using the system. The maximum UAME yield could reach 77 wt.% at 500 °C with atomization feeding. Abstract: Undecylenic acid methyl ester (UAME) was continuously produced from methyl ricinoleate using a microwave-assisted pyrolysis system with atomization feeding. The UAME yield of 77 wt.% was obtained at 500 °C using SiC as the microwave absorbent and heating medium. The methyl ricinoleate conversion and UAME yield from microwave-assisted pyrolysis process were higher than those from conventional pyrolysis. The effect of temperature on the pyrolysis process was also investigated. The methyl ricinoleate conversion increased but the cracking liquid yield decreased when the temperature increased from 460 °C to 560 °C. The maximum UAME yield was obtained at the temperature of 500 °C.